2022
DOI: 10.3390/healthcare10050786
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Physical Predictors of Stress in University Students during the COVID-19 Pandemic: An Observational Study

Abstract: Currently, university students are at a high risk of stress due to university adjustment, educational interruption, and alterations in daily life because of the COVID-19 pandemic. This study examined the relationship of psychosocial and physical factors with stress in university students during the pandemic. Demographic, psychosocial, physical, and self-perceived stress level information were obtained from 409 Thailand university students. A multiple regression analysis was performed, with stress level as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…As a result, their intake of sweets and sugary drinks has increased, and they might even consume these items during study time [ 22 ]. Additionally, previous research has shown that students experienced stress increases during the COVID-19 lockdown due to heavy workloads and long hours spent in front of their computers [ 23 , 24 ]. This stress may also contribute to unhealthy eating habits, such as snacking on sweets and consuming sugary drinks while studying late at night [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, their intake of sweets and sugary drinks has increased, and they might even consume these items during study time [ 22 ]. Additionally, previous research has shown that students experienced stress increases during the COVID-19 lockdown due to heavy workloads and long hours spent in front of their computers [ 23 , 24 ]. This stress may also contribute to unhealthy eating habits, such as snacking on sweets and consuming sugary drinks while studying late at night [ 22 ].…”
Section: Discussionmentioning
confidence: 99%